DIVERSITY OF MICROCHIROPTERANS IN THE THREE HABITATS OF ARGAO WATERSHED FOREST RESERVE, CEBU, PHILIPPINES - Obiso, LS; Alcazar, SMT; Agbay, EA; Alburo, HM; Hoyohoy, GB; Lillo, Lillo; Malaki, AB; Rica, RLV; Manalastas, RDC; Opiniano, RP (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 11 No. 1-2, 2008, 2008)
This study was undertaken to gather information about microchiropteran species composition and diversity in three habitat type (riverine ecosystem, mixed/plantation forest and natural forest) at Argao Watershed Forest Reserve which will serve as a baseline data for conservation program. Mist-netting (1.22 x 6m mist net) were conducted from April 9 – December 27, 2008. A total of two-hundred microchiropteras representing four families in six generas, were captured, process and identified using Key to the Bats of the Philippines (Ingle and Heaney, 1992). Results showed that mixed/plantation forest has the highest diversity among the three habitat types followed by the natural forest and the riverine ecosystem respectively. The top five abundant species are Chaerephon plicata (Wrinkled lipped bat) followed by Rhinolophus inops, Rhinolophus virgo, Rhinolophus arcuatus and Hipposideros diadema. The capture of Chaerephon plicata (Wrinkled lipped bat) must be considered in conservation effort because this specie once form the largest colonies of bats in the Philippines but presently most of its colony are reduced in size or entirely destroyed (Ingle and Heany, 1992).